Understanding tourists’ motives for visiting Malaysia’s national park - Barkhordari, Razieh; Yusof, Aminuddin; Soh, Kim Geok (University of Pitesti, Romania, 2014)
The objective of this study is to identify tourists’ motives for visiting the National Park (Taman Negara) in Malaysia. In addition, this study also seeks to determine if motivational differences exist between foreign and local tourists for visiting Taman Negara. Dann’s (1977) push and pull theory was used as the theoretical framework to examine the motivations of 150 local and foreign tourists visiting Taman Negara. Descriptive analysis and t-tests were used to evaluate quantitative data. Findings demonstrated that tourists were more likely to be motivated by intellectual factors such as discover and learning new things to satisfy their curiosity and expand their knowledge. Comparing tourists’ motivation by their nationality suggest significant differences (p<0.05) between local and foreign tourists. Local tourists are motivated by social, competence and stimulus-avoidance more than foreign tourists.